Masterplan E-Government Pemerintah Kabupaten Bangli - I Wayan Adi Swastama; I Putu Agus Swastika; I Gede Juliana Eka Putra (Primakara University, 2019)
This Bangli Regency Government E-Government Development Master Plan document contains an analysis of the current conditions related to human resources and ICT management organizational structures, conditions of network infrastructure, information and applications as well as elements of funding and existing e-government policies. Subsequently, the vision and mission of e-government was determined which was aligned with the vision and mission of the Bangli Regency Government. The Bangli Regency e-government development blueprint is an important part of the Bangli Regency Government e-government development master plan document which is an ideal model of Bangli Regency Government e-government based on current conditions. This Master Plan contains strategic references that need to be considered in each stage of development towards a development blueprint. Each development strategy is described in stages per year for the next five years based on top priorities and adapts to current conditions and supports the vision and mission of the Bangli District Government.